Protein-alginate gel for enzyme immobilisation - Salleh, Abu Bakar; Mohamed, Suhaila (Kluwer Academic Publishers, 1982)
Propylene glycol alginate forms strong, covalently bonded gel when mixed with certain proteins in alkaline conditions. Enzymes can be immobilised onto the alginate ester before gelating with protein to form the above gel. Some data on the immobilisation of β-glucosidase are presented.